PENENTUAN KERAWANAN BENCANA LONGSOR BERBASIS GIS DI KABUPATEN PESISIR SELATAN - Resti Islami Putri; Novelisa Suryani; Osronita Osronita (Jurnal Azimut, 2023)
The purpose of this study was to determine the distribution of landslide-prone areas and evaluate the suitability of spatial patterns based on landslide vulnerability in Pesisir Selatan Regency. The method is quantitative and descriptive using score classification and parameter weighting used, based on the Puslittanak method (2004). To evaluate the suitability of an area's spatial pattern for landslide hazard using a GIS-based overlay method (ArcGIS 10.3 software). Based on the results of the study, it can be concluded that the Pesisir Selatan region has a low landslide vulnerability of 125788,3 ha (21%), a moderate landslide vulnerability of 455685,8 ha (76%), covering 15 sub-districts, and a high. prone to landslides covering an area of 20293 ha (3%) covering 14 districts. The landslide susceptibility map shows 67% suitable and 33% not suitable. Suitable are advised not to carry out new developments or expansion of land use, and areas that are not suitable need to revise regional spatial patterns, especially in areas prone to high landslides.